Reconciling Bergmann's rule throughout the annual cycle in two congeneric large-bodied migratory waterbirds - Dehai Gu; Yanbo Xie; Tetsuo Shimada; Hiroyoshi Higuchi; Diana Solovyeva; Inga Bysykatova-Harmey; Yanlei Liu; Junjian Zhang; Qingshan Zhao; Lei Cao; Anthony D. Fox (Avian Research)
Bergmann's rule predicts that the larger of two homeotherm species differing only in size would occur at higher latitudes, or in cooler climates than the smaller, because of relative thermoregulatory costs in relation to body mass/surface area ratio. Individual tracking data from two congeneric long-distance migratory northern nesting swan species, Tundra Cygnus columbianus (TS, n = 99) and Whooper Swans C. cygnus (WS, 61–71% larger mass than TS, n = 47) were used to determine their summering and wintering latitudes along similar migration routes and common staging areas along the same flyway. We hypothesised that throughout Arctic and Boreal breeding areas (10 °C in July), summer ambient temperatures mainly exceed the Lower Critical Temperatures (LCT, c. 1 °C) for both swan species, so the duration of the snow-free summer period will favour smaller body size at highest latitudes, since this constrains the time available to lay, incubate eggs and raise cygnets to fledging. We hypothesised that in contrast, in winter, both species occur in temperatures near to freezing (−3 °C in January), below their respective LCT, so differential thermoregulation demands would constrain TS to winter south of WS. Tracking of individuals showed for the first time that while smaller TS summered significantly north of WS, WS wintered significantly north of TS, with limited overlap in both seasons. We conclude that differences in relative summer distribution of these two closely related migratory herbivores are not to do with latitude per se but are constrained by the time both species require to raise their young to fledging during the short northern summer, when thermoregulation costs are unlikely limiting. In winter, both swan species occur within a climate envelop at or below their respective LCT and smaller TS occurred consistently south of the range of the tracked WS, as predicted by Bergmann's rule.